Randomised controlled trial of silk therapeutic garments for the management of atopic eczema in children: the CLOTHES trial - Thomas, Kim S.; Bradshaw, Lucy; Sach, Tracey H.; Cowdell, Fiona; Batchelor, Jonathan M.; Lawton, Sandra; Harrison, Eleanor F.; Haines, Rachel H.; Ahmed, Amina; Dean, Taraneh; Burrows, Nigel P.; Pollock, Ian; et al. (NIHR Journals Library, 2017)
Background: Atopic eczema (AE) is a chronic, itchy, inflammatory skin condition that affects the quality of life of children and their families. The role of specialist clothing in the management of AE is poorly understood. Objectives: To assess the effectiveness and cost-effectiveness of silk garments for the management of AE in children with moderate to severe disease. Design: Parallel-group, observer-blind, randomised controlled trial of 6 months’ duration, followed by a 2-month observational period. A nested qualitative study evaluated the beliefs of trial participants, health-care professionals and health-care commissioners about the use of silk garments for AE. Setting: Secondary care and the community in five UK centres. Participants: Children aged 1–15 years with moderate or severe AE. Interventions: Participants were randomised (1 : 1 using online randomisation) to standard care or standard care plus 100% silk garments made from antimicrobially protected knitted sericin-free silk [DermaSilkTM (AlPreTec Srl, San Donà di Piave, Italy) or DreamSkinTM (DreamSkin Health Ltd, Hatfield, UK)]. Three sets of garments were supplied per participant, to be worn for up to 6 months (day and night). At 6 months the standard care group received the garments to use for the remaining 2-month observational period. Main outcome measures: Primary outcome – AE severity using the Eczema Area and Severity Index (EASI) assessed at 2, 4 and 6 months, by nurses blinded to treatment allocation. EASI scores were log-transformed for analysis. Secondary outcomes – patient-reported eczema symptoms (Patient Oriented Eczema Measure); global assessment of severity (Investigator Global Assessment); quality of life of the child (Atopic Dermatitis Quality of Life, Child Health Utility – 9 Dimensions), family (Dermatitis Family Impact Questionnaire) and main carer (EuroQoL-5 Dimensions-3 Levels); use of standard eczema treatments (e.g. emollients, topical corticosteroids); and cost-effectiveness. The acceptability and durability of the clothing, and adherence to wearing the garments, were assessed by parental/carer self-report. Safety outcomes – number of skin infections and hospitalisations for AE. Results: A total of 300 children were randomised (26 November 2013 to 5 May 2015): 42% female, 79% white, mean age 5 years. The primary analysis included 282 out of 300 (94%) children (n = 141 in each group). Garments were worn for at least 50% of the time by 82% of participants. Geometric mean EASI scores at baseline, 2, 4 and 6 months were 8.4, 6.6, 6.0, 5.4 for standard care and 9.2, 6.4, 5.8, 5.4 for silk clothing, respectively. There was no evidence of difference between the groups in EASI score averaged over all follow-up visits adjusted for baseline EASI score, age and centre (ratio of geometric means 0.95, 95% confidence interval 0.85 to 1.07; p = 0.43). This confidence interval is equivalent to a difference of –1.5 to 0.5 in the original EASI scale units. Skin infections occurred in 39 out of 141 (28%) and 36 out of 142 (25%) participants for standard care and silk clothing groups, respectively. The incremental cost per QALY of silk garments for children with moderate to severe eczema was £56,811 from a NHS perspective in the base case. Sensitivity analyses supported the finding that silk garments do not appear to be cost-effective within currently accepted thresholds. Limitations: Knowledge of treatment allocation may have affected behaviour and outcome reporting for some of the patient-reported outcomes. Conclusions: The addition of silk garments to standard AE care is unlikely to improve AE severity, or to be cost-effective compared with standard care alone, for children with moderate or severe AE. This trial adds to the evidence base to guide clinical decision-making. Future work: Non-pharmacological interventions for the management of AE remain a research priority among patients.